2001
DOI: 10.1093/jac/47.5.611
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid penetration and pharmacokinetics of levofloxacin in an experimental rabbit meningitis model

Abstract: This study was designed to investigate the penetration across the blood-brain barrier of three doses of levofloxacin using a microdialysis probe implanted into the cerebrospinal fluid (CSF) of a rabbit pneumococcal meningitis model. The microdialysis guide cannula was implanted into rabbit subarachnoid space using a stereotaxic frame. After 3 days, 10(4) cfu Streptococcus pneumoniae serotype 3 in 0.3 mL saline was injected via intracisternal puncture and animals were allowed to incubate the organisms for 16-18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
27
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 17 publications
13
27
5
Order By: Relevance
“…Levofloxacin (human pharmaceutical product, Tavanic (0.5% levofloxacin); Hoechst Marion Roussel Ltd, Mumbai, India) was administered at a dose rate of 4 mg/kg body weight into the left jugular vein. The dosage level of levofloxacin employed in the present study was comparable to the intravenous dose of the drug used by previous workers in rabbits (Destache et al, 2001) and humans (Langtry and Lamb, 1998) to study the pharmacokinetics of levofloxacin.…”
Section: Experimental Animals and Drug Administrationmentioning
confidence: 59%
See 1 more Smart Citation
“…Levofloxacin (human pharmaceutical product, Tavanic (0.5% levofloxacin); Hoechst Marion Roussel Ltd, Mumbai, India) was administered at a dose rate of 4 mg/kg body weight into the left jugular vein. The dosage level of levofloxacin employed in the present study was comparable to the intravenous dose of the drug used by previous workers in rabbits (Destache et al, 2001) and humans (Langtry and Lamb, 1998) to study the pharmacokinetics of levofloxacin.…”
Section: Experimental Animals and Drug Administrationmentioning
confidence: 59%
“…About 80% of a dose is found in the urine as unchanged drug and ≤5% as inactive metabolites (Langtry and Lamb, 1998). The pharmacokinetics of levofloxacin has been investigated in humans (Verho et al, 1996;Amsden et al, 1999;Chulavatnatol et al, 1999;Gascon et al, 2000), rabbits (Mochizuki et al,1994;Destache et al, 2001), rats (Ito et al, 1999) and guinea pigs (Edelstein et al, 1996). However, there is no information available on the pharmacokinetics of levofloxacin in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental meningitis model, Destache and coworkers (8) found that the average level of CSF exposure to levofloxacin ranged between 53 and 76% of the corresponding level of plasma exposure in rabbits chal- on May 10, 2018 by guest http://aac.asm.org/ lenged with S. pneumoniae. Likewise, in a previous study (32), based on a single sampling time during a diagnostic lumbar puncture in patients with acute bacterial meningitis treated with a combination of a beta-lactam plus levofloxacin at 500 mg b.i.d.…”
Section: Discussionmentioning
confidence: 99%
“…Previous pharmacokinetic studies documented that levofloxacin could adequately penetrate the cerebrospinal fluid (CSF) in the presence of meningeal inflammation both in animals and in humans (8,32). However, ratios of the concentration in CSF to the concentration in plasma (CSF to plasma concentration ratios) may vary substantially according both to different sampling times and to the status of the blood-CSF barrier.…”
mentioning
confidence: 99%
“…The use of this model greatly helped the understanding of several aspects of pneumococcal meningitis, including bacterial replication in the CSF, host defenses and inflammation, BBB alteration, and also the systemic effects of meningitis on animal respiration and circulation (236). Numerous studies have been undertaken to evaluate antibiotic efficacy (34,64,73,85,172,189,203,226,231) and the role of host and bacterial factors in disease pathogenesis (10,36,247). Interestingly, the effectiveness of a bactericidal but nonbacteriolytic antibiotic, such as daptomycin, in clearing pneumococcal infection from the CSF and in reducing inflammation was proven by means of both this rabbit model (226) and a previously described rat model (94).…”
Section: Rat and Rabbit Modelsmentioning
confidence: 99%